Drinking patterns and the distribution of alcohol-related harms in Ireland: evidence for the prevention paradox - Claire O'Dwyer; Deirdre Mongan; Seán R. Millar; Marion Rackard; Brian Galvin; Jean Long; Joe Barry (BMC, 2019)
Abstract Background According to the prevention paradox, the majority of alcohol-related harms in the population occur among low-to-moderate risk drinkers, simply because they are more numerous in the population, although high-risk drinkers have a higher individual risk of experiencing alcohol-related harms. In this study we explored the prevention paradox in the Irish population by comparing alcohol-dependent drinkers (high-risk) to low-risk drinkers and non-dependent drinkers who engage in heavy episodic drinking (HED). Methods Data were generated from the 2013 National Alcohol Diary Survey (NADS), a nationally representative cross-sectional survey of Irish adults aged 18-75. Data were available for 4338 drinkers. Respondents dependent on alcohol (as measured by DSM-IV criteria), respondents who engaged in monthly HED or occasional HED (1-11 times a year) and low-risk drinkers were compared for distribution of eight alcohol-related harms. Results Respondents who were dependent on alcohol had a greater individual risk of experiencing each harm (p < .0001). The majority of the harms in the population were accounted for by drinkers who were not dependent on alcohol. Together, monthly and occasional HED drinkers accounted for 62% of all drinkers, consumed 70% of alcohol and accounted for 59% of alcohol-related harms. Conclusions Our results indicate that the majority of alcohol consumption and related harms in the Irish population are accounted for by low- and moderate-risk drinkers, and specifically by those who engage in heavy episodic drinking. A population-based approach to reducing alcohol-related harm is most appropriate in the Irish context. Immediate implementation of the measures in the Public Health (Alcohol) Act (2018) is necessary to reduce alcohol-related harm in Ireland.